A Wideband and Polarization-Independent Metasurface Based on Phase Optimization for Monostatic and Bistatic Radar Cross Section Reduction - Jianxun Su; Yao Lu; Zengrui Li; Rongrong Zhang; Yaoqing (Lamar) Yang (International Journal of Antennas and Propagation)
A broadband and polarization-independent metasurface is analyzed and designed for both monostatic and bistatic radar cross section (RCS) reduction in this paper. Metasurfaces are composed of two types of electromagnetic band-gap (EBG) lattice, which is a subarray with “0” or “π” phase responses, arranged in periodic and aperiodic fashions. A new mechanism is proposed for manipulating electromagnetic (EM) scattering and realizing the best reduction of monostatic and bistatic RCS by redirecting EM energy to more directions through controlling the wavefront of EM wave reflected from the metasurface. Scattering characteristics of two kinds of metasurfaces, periodic arrangement and optimized phase layout, are studied in detail. Optimizing phase layout through particle swarm optimization (PSO) together with far field pattern prediction can produce a lot of scattering lobes, leading to a great reduction of bistatic RCS. For the designed metasurface based on optimal phase layout, a bandwidth of more than 80% is achieved at the normal incidence for the −9.5 dB RCS reduction for both monostatic and bistatic. Bistatic RCS reduction at frequency points with exactly 180° phase difference reaches 17.6 dB. Both TE and TM polarizations for oblique incidence are considered. The measured results are in good agreement with the corresponding simulations.